Effect of Classical Turkish Music on Pain and Anxiety of Patients undergoing Bone Marrow Aspiration and Biopsy: A Randomized Controlled Clinical Trial - Eda Ergin; Fatma Kahriman; Hatice Coşan Ay; Şebnem Çınar Yücel (Journal of Holistic Nursing and Midwifery)
Introduction: Bone Marrow Aspiration and Biopsy (BMAB) is a painful procedure that can causes anxiety in patients. Music can help reduce pain and anxiety levels in patients by directing their attention from negative stimuli towards pleasant and encouraging thoughts. Objective: This study aims to determine the effect of classical Turkish music on pain and anxiety of patients undergoing BMAB. Materials and Methods: This is a randomized, controlled trial conducted on 68 patients undergoing BMAB who were selected from the hematology outpatient clinics in a hospital in İzmir, western Turkey. They were randomly divided into two groups of control (n=34) who received the general procedure only and the music group (n=34) who listened to classical Turkish music for 15 minutes before the procedure. Data were collected using a demographic form, Visual Analogue Scale (VAS), and State Anxiety subscale of Spielberger’s State-Trait Anxiety Inventory. Chi-square was used for comparing categorical variables, and t-test and ANOVA ​​were used for comparing numerical variables. Bonferroni test was used for post hoc comparisons. A P<0.05 statistically significant. In case of a significant difference between the groups, Cohen’s d effect size was calculated. Results: In the music group (Mean±SD age=63.73±14.81 years), 62% were male, 71% were married, 76% had a secondary education or lower, and 49.1% reported that biopsy was for diagnostic purposes. In the control group (Mean±SD age=51.76±19.45 years), 50% were female, 53% were married, 62% had a secondary education or lower, and 50.9% reported that biopsy was for diagnostic purposes. A statistically significant difference was found in the mean VAS scores of both groups before and after the treatment (P=0.001). A significant difference was found in the state anxiety level only in the music group before and after the treatment (P=0.003). Conclusion: Classical Turkish music prior to BMAB can reduce the pain and anxiety of patients. It is recommended for nurses to use music therapy to reduce the pain and anxiety of patients undergoing BMAB.